Mesenteric cysts: A rare case - Asgharnia, Maryam; Rahbar, Tayebeh; Heirati, Seyedeh Fatemeh Dalil (Clinical Journal of Obstetrics and Gynecology, 2019)
Mesenteric cysts are rare benign intra-abdominal tumors with an incidence of 1 case per 250,000 hospital admission. This lesion occurs most frequently in women in the reproductive period.The etiology of such cysts remains unknown but several theories regarding their development exist. Most of these lesions present with vague abdominal pain and nausea. Less commonly they will present with bowel obstruction due to external compression. The diagnosis of these tumors is by abdominal ultrasound or computed tomography. We report a case of Mesenteric cyst in 51-year-old female patient.